1988
DOI: 10.1055/s-2006-962544
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents ofEugenia unifloraLeaf Oil1

Abstract: The essential oil of the leaves of Eugenia uniflora L. (Myrtaceae) was investigated by GLC, NMR, and mass spectrometry. Main constituents are furanodiene (27a), and the hitherto unknown selina-1,3,7(1 1)-trien-8-one (36) and oxidoselina-1 ,3,7(1 1)-trien-8-one (41). The oil contains almost no monoterpenes, but several known sesquiterpenes. The characteristic odor of the oil is determined by the mushroom-like, woody, and spicy smelling furanodiene (27a), and by the green and cucumber note of selinatrienone (36). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 3 publications
5
63
2
5
Order By: Relevance
“…It may also reduce weight, blood pressure, and serve as a diuretic (ADEBAJO; OLOKI; ALADESANMI, 1989). Pitanga fruits, also known as Brazilian cherry or Suriname cherry, contain various volatile compounds that are also found in the essential oil of pitanga leaves (WEYERSTAHL et al, 1988;OLIVEIRA et al, 2006). Like the leaves, pitanga fruits may also have health benefits.…”
Section: Determination Of Fatty Acid Compositionmentioning
confidence: 99%
“…It may also reduce weight, blood pressure, and serve as a diuretic (ADEBAJO; OLOKI; ALADESANMI, 1989). Pitanga fruits, also known as Brazilian cherry or Suriname cherry, contain various volatile compounds that are also found in the essential oil of pitanga leaves (WEYERSTAHL et al, 1988;OLIVEIRA et al, 2006). Like the leaves, pitanga fruits may also have health benefits.…”
Section: Determination Of Fatty Acid Compositionmentioning
confidence: 99%
“…The fragments were collected from 40 to 450 u. Identification of oil components was based on the Kovats index, comparison of their mass spectral fragmentation patterns with the Mass Spectra libraries (Wiley 139, 275 and 7 and Nist 127), published data (Weyerstahl et al, 1988;Henriques et al, 1993;Lima et al, 1993;Morais et al, 1996;Maia et al, 1999;Ogunwande et al, 2005;Melo et al, 2007;Costa et al, 2009Costa et al, , 2010Peixoto et al, 2010) and myrrh essential oil injection (Mölleken et al, 1988). The GC-MS quantification was obtained using the total ions chromatogram (TIC) and was expressed as an average of the data obtained for three samples of extracted leaf oil.…”
Section: Gas Chromatography Mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…Several studies have examined the composition of oil from the leaves of E. unifl ora L. from different regions in Brazil and other countries (Weyerstahl et al, 1988;Morais et al, 1996;Henriques et al, 1996;Maia et al, 1999;Holetz et al, 2002;Melo et al, 2007;Costa et al, 2009;Peixoto et al, 2010). Such studies have shown that in the essential oil of pitangueira leaves the composition and concentration of components are very complex.…”
Section: Introductionmentioning
confidence: 99%
“…There are over 500 species in the genus, out of which 400 are indigenous plants found in Brazil 1 . Eugenia uniflora is a fruit-bearing plant commonly known as Surinam cherry, Brazilians 2 . This fruit, Eugenia uniflora has great economic importance in South American countries most especially in Brazil for its use in the food industry, for the production of frozen pulp and juice.…”
Section: Introductionmentioning
confidence: 99%